Knowledge Management System Dalam Peningkatan Mutu Pemeliharaan Jaringan Distribusi Tenaga Listrik Berbasis Supervisory Control And Data Acquisition - Eva Argarini Pratama - AMIK BSI Purwokerto (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract   The existence of SCADA systems (Supervisory Control and Data Acquisition) can help the operator to set the electrical system that the authority is centralized in a Control Center. Power to Control Center is determined by the reliability of the SCADA system and telecommunications channels that support it, such as by means of a decision or action can be taken more quickly and accurately to the electrical system in case something such as interference. But the problem is interference often occurs on the basic functions of SCADA as in TS (Telesignalling), TM (Telemetering), TC (telecontrol) that is not working properly, but if an interruption is too long at one of the basic functions, it will be difficult for the operator in determining the power, transfer, and the existing supply the electrical system. For that we need a Knowledge Management System (KMS), which manages the knowledge of the owner of the tacit knowledge about this that makes performance in improving the quality of maintenance of the distribution network of electric power, it must also be an impact on service improvement power availability to the general public.   Keywords: SCADA, KMS, Control Center, Maintenance, Electrical.